Cumulative socio‐economic disadvantage and traumatic dental injuries during adolescence. Issue 2 (4th December 2020) - Mira, Rolla Saud; Marcenes, Wagner; Stansfeld, Stephen A.; Bernabé, Eduardo
Abstract: Background/aim: Studies on the association between socio‐economic circumstances and traumatic dental injuries (TDIs) are cross‐sectional and inconclusive. The aim of this study was to investigate the association between cumulative socio‐economic disadvantage and TDIs among adolescents. Method: Data from 668 participants in the East London Adolescents Community Health Survey (RELACHS) were analysed. Family socio‐economic indicators (parental employment, car ownership and eligibility for free school meals) were collected when participants were in grades 7 (11‐12 years), 9 (13‐14 years) and 11 (15‐16 years). The number of periods (RELACHS waves) adolescents lived in socio‐economic disadvantage was counted for each socio‐economic measure, ranging from 0 (never in disadvantage) to 3 (always in disadvantage). Adolescents were dentally examined for TDIs at age 15‐16 years. The association between each measure of cumulative socio‐economic disadvantage and TDIs was tested in logistic regression models adjusting for demographic factors. Results: Significant positive linear trends in the prevalence of TDIs were observed by the number of periods of parental unemployment and being without a family car, but not by eligibility for free school meals. Adolescents whose parents were always unemployed had 2.06 (95% CI: 1.12‐3.80) greater odds of having TDIs than those whose parents were never unemployed. Similarly, adolescents from families that never owned a car had 2.17 (95% CI: 1.26‐3.74) greater odds of having TDIs than those that always had a family car. Conclusion: Cumulative socio‐economic disadvantage during adolescence was associated with greater odds of having TDIs.